Karyoptosis: A novel type of cell death caused by chronic autophagy inhibition. Issue 4 (3rd April 2018) - Baron, Olga; Fanto, Manolis
ABSTRACT: Macroautophagy/autophagy influences onset and progression of several human neurodegenerative diseases, because of its critical role as a regulator of neuronal proteostasis and organelle quality control. In many neurodegenerative diseases, impairment in autophagy is thought to play a fundamental part in the terminal phases of cellular degeneration and death. However, the ultimate mechanism of neuronal cell death remains elusive. In a recent study we have identified a new form of regulated cell death, which arises upon autophagy inhibition.